N024 Changing face of care for patients with moderate-to-severe inflammatory bowel disease: The role of specialist nurses in the governance of anti-TNFα prescribing in Romania. (16th January 2018) - Leca, A S; Timofte, O; Mihnea, D; Melinte, N; Balan, G G; Stanciu, C
Abstract: Background: Anti-tumour necrosis factor (TNF) therapy is highly effective for inﬂammatory bowel disease (IBD). Rigorous supervision prior to and during anti-TNFα treatment is required to screen and monitor patients for adverse events. It is necessary to ensure on-going therapy is uninterrupted; therefore, IBD nurses are essential components of multidisciplinary IBD services, but their role in facilitating the safe delivery of anti-TNFα drugs is unacknowledged. Methods: The aim of the study was to determine the impact of IBD nurses on anti-TNFα treatment and therapeutic response, after initiating the IBD nurses' assistance programme on 1st January 2017. Activities related to anti-TNFα governance were prospectively assessed by questionnaire among IBD patients in an university clinic. A total number of 20 patients with IBD and anti-TNFα treatment were involved during January-June 2017. For each one of them, there were noted the frequency of medical visits to the gastroenterologist concerning potentially adverse effects of the therapy, before and after starting the follow-up programme involving IBD-nurses. Results: On average, after IBD nurses started to follow-up the patients, the number of medical visits to gastroenterologist decreased to 40 % in 6 months. Each patient evaluated the nurse's ability to answer his questions, and the way this improved the quality of life and fulfilled his expectations. 40% of patients declared an improvement of their life quality in the last 6 months. Conclusions: Anti-TNF therapy governance is an essential quality component of IBD care. IBD nurses are best positioned to undertake this role, improving the management of patients treated with anti-TNFα agents and following them up for potential side effects.